2010
DOI: 10.1007/s10344-009-0361-5
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection of an expanding beaver (Castor fiber) population in central and upper Morava River basin

Abstract: Habitat selectivity by European beaver (Castor fiber L., 1758) was studied in 226 km of river channels during their colonization of the Morava River basin (the Czech Republic), which had not been occupied by beavers for hundreds of years. The colonization started after initial reintroductions in 1991 and 1992. Annual increases in colonization of the river system from 1995 to 2007 were 15.5±9.4 SD km year −1 and varied greatly between these years (min 0 km, max 33 km). Beavers appeared to be following a dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 31 publications
6
28
0
2
Order By: Relevance
“…Single groups are relatively recently established on two more watersheds, and these have both selected high quality habitat patches. This pattern is in accordance with other studies, which show a pattern of rapid colonization within watersheds, strong selection for the highest quality unoccupied habitat available, progressive lowering of the quality of habitat on which settlement occurs as a watershed population grows, and a strong barrier effect of watershed divides on dispersal (Hartman 1994(Hartman , 1995Fustec et al 2001;John et al 2010;Halley et al 2002 for review). Beavers are known to have colonised site 2, on Skjenaldelva watershed, within 5 years of the initial release on Ingdalselva.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Single groups are relatively recently established on two more watersheds, and these have both selected high quality habitat patches. This pattern is in accordance with other studies, which show a pattern of rapid colonization within watersheds, strong selection for the highest quality unoccupied habitat available, progressive lowering of the quality of habitat on which settlement occurs as a watershed population grows, and a strong barrier effect of watershed divides on dispersal (Hartman 1994(Hartman , 1995Fustec et al 2001;John et al 2010;Halley et al 2002 for review). Beavers are known to have colonised site 2, on Skjenaldelva watershed, within 5 years of the initial release on Ingdalselva.…”
Section: Discussionsupporting
confidence: 91%
“…The topography and vegetation in the gorge is such that beavers could live in burrows with few obvious signs of presence, so it is possible these beavers may have been descendants of a remnant of the original population which survived at this location. Colonising beavers usually either occupy sites adjacent to existing territories, or make longer distance dispersals to patches of high quality habitat some distance from existing territories (Fustec et al 2001;John et al 2010;Halley & Rosell 2002 for review). The pattern in Ulsberg-Voll from the 1930s-1970s is consistent with shortdistance colonisations from a refuge in the gorge, which is then noted by the human population of the wider-bottomed river valley below.…”
Section: Discussionmentioning
confidence: 99%
“…Such density-dependent habitat selection has been very well studied in rodents (Halama and Dueser 1994;Messier et al 1990;Morris 1989), and RSFs have been increasingly used to study density dependent habitat selection (McLoughlin et al 2010;van Beest et al 2014). John et al (2010) studying the expansion of a reintroduced population of the European Beaver did also observed changes in habitat selection over time. Still, those changes were related to vegetation features rather than geomorphology as we show in this study.…”
Section: Discussionmentioning
confidence: 96%
“…But near carrying capacity, beaver colonies could be settling in suboptimal sites that other beavers left unutilized. For instance, John et al (2010) found reintroduced European beavers (Castor fiber) were more likely to settle in areas with steeper gradients, smaller watersheds, and closer to roads 12 years after their initial release. Recent spread of beavers in the Patagonian steppe sets up a unique scenario to test this hypothesis.…”
Section: Introductionmentioning
confidence: 97%
“…In the dispersal phase, beavers follow a logistic population growth pattern with a characteristic dampening as the population approaches carrying capacity (Bartak et al 2013). In recent decades, after nearly a half-century of absence, beavers have rapidly colonized their historical distribution (Rosell et al 2012), making them a useful model species for characterizing the process of habitat selection in different stages of a population development (Hartman 1995, Pinto et al 2009, John et al 2010, Swinnen et al 2017.…”
Section: Introductionmentioning
confidence: 99%